(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
One of the effective methods for developing and regulating the labor market is a systematic analysis of criteria assessing supply and demand in the labor market. In the process of digitalization, the labor market is undergoing transformations in all directions and one of the most important tasks is to train highly qualified specialists in the field of digital technologies for the global and national labor markets. The article is devoted to the author’s approach to developing criteria for assessing the demand and supply of specialists in the field of digital technologies in the labor market of Uzbekistan.